Capital Structure, Value of the company and Profitability: The case of the Food Sector companies in Peru: 2009-2013 - Cortez Cortez, Gaby (2015)
The work has proposed trough the specification of a model to test the consistency of the objective of creating corporate value considering three main determinants: growth, profitability and leverage. Preliminary results confirm the general hypotheses in the research.The most important variables in the work are related to the company’s financial liabilities and their capital stock that together and combined forms the capital structure.The extent to which the firm borrows determines its capital structure. While there is no recipe for finding the optimal degree of the capital structure, the exchange between debt and equity offers insight into the changes in the risk facing the company and its expected return. In theoretical terms more debt increases the risk and higher return is expected. If companies increase their debt they assume greater risk leading a drop in the share price and higher returns are expected. These theoretical approaches linked to the established hypotheses are part of the body work.The sample of companies studied are in the food sector of the Peruvian economy, highlighting the sugar companies (Casa Grande, Laredo and Paramonga), dairy sector (Gloria and Laive), canned fish sector (Austral Group), and food in various sectors (Alicorp); all listed its shares on the Lima Stock Exchange.